Peter the Great and the North German Duchies in the Early 18th Century: Between Dynastic Considerations and Economic Interests Pierre le Grand et les duchés du Nord au début du XVIIIe siècle: Entre considérations dynastiques et intérêts économiques - Félicité, Indravati (Revue de synthese / Centre international de synthese, 2019)
In the early 18th century, Peter the Great forms dynastic alliances with German princes. The article begins with an analysis of the preliminary negotiations to these alliances. The study also focuses on how these weddings were made public and how the reports on this marriage were perceived and interpreted in contemporary publications dealing with the diplomatic aspects of these alliances. The article concludes with an examination of the perception of these events by contemporary observers and the representation of this event in 18th-century journals.
CRIS-Team Scopus Importer:2024-04-04
Keywords: ceremonial; integration; newspapers; scholarly publications